Anthocyanin, nutrient contents, and antioxidant activity of black rice bran of Oryza sativa L. ‘Cempo Ireng’ from Sleman, Yogyakarta, Indonesia - Pratiwi Apridamayanti; Rarastoeti Pratiwi; Yekti Asih Purwestri; Woro Anindito Sri Tunjung; Rumiyati Rumiyati (Indonesian Journal of Biotechnology, 2017)
The chemical contents and health benefits of black rice bran of some rice cultivars have been investigated. However, there has been little research on the ‘Cempo Ireng’ cultivar from Sleman, Yogyakarta. The aim of this present study was to determine the anthocyanin, antioxidant activity, and macro- and micronutrients contents of black rice bran from this local cultivar. The anthocyanin in the black rice bran was extracted using the maceration method with methanol as a solvent. The extract obtained was separated through a preparative thin layer chromatography (TLC) of silica GF254 and a mobile phase composed of n-butanol, acetic acid, and water. Two fractions were collected and analyzed for the anthocyanin content. The preparative TLC spots were separated for further detection and measurement of cyanidin 3-O-glucoside using HPLC followed by LC-MS. The antioxidant activity of the fractions were measured using the DPPH free radical scavenging method. The results showed that the anthocyanin in fraction 1 was identified as cyanidin 3-O-glucoside (66.1 ± 10.6 µg/g). The IC50 of fractions 1 and 2 were 200.96 and 218.36 µg/mL, respectively. Analysis of the macro- and micronutrients revealed that the black rice bran of ‘Cempo Ireng’ had nutrient contents comparable with other rice cultivars. Therefore, this local black rice bran can be used as a source of antioxidants and macro-- and micronutrients.